Preparation and in-vitro / in-vivo Characterization of Transdermal Amphiphilogel Loaded with Biodegradable Polymeric Submicron Carriers of Meloxicam for Treatment of Inflammation - Singhavi, Dilesh Jagdish; Yeole, Pramod; Khan, Shagufta (Indian Journal of Pharmaceutical Education and Research, 2022)
Aim: The main purpose for this study was to develop and evaluate amphiphilogels loaded with meloxicam-submicron particles considering the benefits of the transdermal route of administration of anti-inflammatory drugs (nonsteroidal). Materials and Methods: Glyceryl monostearate (7%, 9% and 11% w/w) and sorbiton monostearate (span 60; 21%, 23% and 25% w/w) amphiphilogels containing meloxicam-submicron particles equivalent to 0.5% w/w drug were formulated. Then these were evaluated through rheological, in-vitro permeation, in-vitro release, pharmacokinetics, pharmacodynamics and skin irritation studies. The rodents were chosen as subjects to conduct the pharmacokinetics study of meloxicam via oral administration and transdermally as solutions and gels, respectively. Results: It was observed that the Cmax value of drug obtained from meloxicam solution and a marketable piroxicam gel formulation were radically lower than that obtained from an amphiphilogel (FM4, containing 7% w/w glyceryl monostearate). It was also observed that when applied transdermally, the bioavailability of meloxicam from FM4 was higher (n = 3, p< 0.001) than 2.5 times the bioavailability of meloxicam from a solution which was orally administered. The anti-inflammatory property of FM4 was comparatively much greater than the commercially available formulations in carrageenaninduced edema in rat’s paw. Conclusion: It can be concluded that the amphiphilogels loaded with meloxicam-submicron particles was found to be a safe and efficient drug delivery system for enhanced transdermal delivery of meloxicam.
Keywords: Transdermal; Submicron carriers; Ampiphilogel; Bioavailability; Antiinflammatory